Hubungan Jenis Ketuban Pecah Dini dengan Berat Bayi Lahir dan Kebutuhan Perawatan Neonatal Intensif - Kasyafiya; Zumroh Hasanah; Amelia Indah Roswanah (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2026)
Introduction: Premature rupture of membranes is a major obstetric complication that contributes significantly to increased neonatal morbidity and mortality. Objective: This study aims to analyze the relationship between types of premature rupture of membranes (premature rupture of membranes [PROM] and preterm premature rupture of membranes [PPROM]) with birth weight and Neonatal Intensive Care Unit (NICU) care requirements. Method: This quantitative observational analytic study utilized a cross-sectional approach with a total sampling technique involving 375 mothers with premature rupture of membranes at RSUD Tangerang from 2020 to 2025. Secondary data were gathered from medical records and analyzed using Fisher's Exact Test. Results: The majority of respondents experienced PPROM (79.7%), gave birth to low birth weight (LBW) infants (80.3%), and did not require NICU admission (65.3%). Bivariate analysis revealed that all PPROM cases (100%) resulted in LBW infants and 43.1% required NICU care, whereas in the PROM group, only 2.6% were LBW and 1.3% required NICU care. There was a significant relationship between the type of premature rupture of membranes and birth weight (p < 0.001) as well as the need for NICU care (p < 0.001). Conclusion: The type of premature rupture of membranes is significantly associated with birth weight and NICU care needs, with PPROM markedly increasing the risk of LBW and the necessity for neonatal intensive care.